Functional characteristics of tissue equivalents of various tissues using porous-permeable incubators of titanium nickelide - O. V. Kokorev; V. N. Khodorenko; G. T. Dambaev; V. E. Gunther (Acta Biomedica Scientifica, 2015)
Pancreas cages form a functional fabric and allocate hormonal substances necessary for indemnification of the lost structures of a pancreas of an organism. And, at input in an organism of ß-cells deprived of a substrate, life cycle transplanted xenogeneic cages considerably decreases under the influence of immune factors, during too time of a cage in an incubator function longer time, promoting construction of spatial architecture of new gland. The given methodology is effective in diabetes treatment as the transplanted cages it is very thin react to allocation of insulin depending on a condition homeostatic organism systems that is an actual problem at introduction of injections of insulin. Results of researches show that incubators of titanium nickelide are highly effective for their use as biocompatible matrixes. Features incubator spaces, and also a material titanium nickelide the titan promote creation fabric biosystems from various cages of an organism and to considerable prolongation of functional activity transplantation cages that accordingly conducts to increase in period of validity of therapeutic effect. Investigation have shown the formation of specific tissues in porous-permeable incubators of titanium nickelide for different cell populations. Allogeneic bone marrow cells immobilized in incubators of titanium nickelide possess antitumor (25%) and significant antimetastatic (45%) effect. The study of morphological parameters immunocompetent organs showed that administration of allogeneic bone marrow cells can decrease thymic regression, reduces splenomegaly in animals with transplantable tumors. Hepatocytes were implanted in porous materials of titanium nickelide mice with CCl4-induced hepatitis provided significant antitoxic effect. Obtained initial results promising pancreatic tissue-engineering in complex treatment of diabetes. It is noted that the use of incubators permeable porous nickel-titanium increase therapeutic effect and significantly prolongs effect of transplanted cells, as opposed their injecting.